Renewable Energy Source: An Overview - Ahmed, Syed Siraj; Ahmed, Momin Faisal (IJRDO-Journal of Applied Science, 2016)
Energy has been a vital input into the economic and social development. It is the gift of the nature to the mankind in various forms. The consumption of the energy is directly proportional to the progress of the mankind. However, one third of the world population, living in developing and threshold countries, has no access to electricity. These people mostly live in remote and rural areas with low population density, lacking even the basic infrastructure. Accordingly, utility grid extension is not a cost-effective option and sometimes technically not feasible. Therefore, it is imperative to look for sustainable (that is., cost-effective, environmentally benign and reliable) sources of energy for the development of these regions. The primary source of energy is fossil fuel, however the finiteness of fossil fuel reserves and large scale environmental degradation caused by their widespread use, particularly global warming, urban air pollution and acid rain, strongly suggests that harnessing of non-conventional, renewable and environment friendly energy resources is vital for steering the global energy supplies towards a sustainable path. This paper describes in brief the non-conventional energy sources and their usage in India.